What it takes to win when the game is rigged: the evolution of opposition electoral strategies in Moscow, 2012–2017. Issue 6 (18th August 2019) - Gorokhovskaia, Yana
ABSTRACT: This paper examines how the political opposition innovated strategies to overcome obstacles presented by Russia's uneven electoral playing field. Using evidence from two municipal elections in Moscow, I argue that members of the opposition have coordinated around local contests in response to political opportunities created by the Kremlin, including the anti-electoral fraud protests of the winter of 2011–2012 and the resurrection of gubernatorial elections in 2012. Following these openings, grassroots electoral initiatives recruited and trained opposition-minded individuals, first focusing on established activists and then on politicized individuals, to run for municipal council seats. The campaigns provided training using ad hoc educational seminars and later developed electronic tools that lowered barriers to political participation. As a result of these campaigns, electoral competition has boomed at the local level in Moscow even as regional and national contests have become less competitive. The campaigns demonstrate the continued vulnerability of authoritarian regimes that rely on elections for political legitimacy. Furthermore, the development of highly portable online tools for campaigning has potentially long-term democratizing consequences.